Proposed financial ratios and indicators to measure unlawful gain in Islamic financial institutions An applied study on Faisal Islamic Bank of Egypt - Yousef, Osama Abdelmonge (Journal of Economic, Administrative and Legal Sciences, 2020)
The study of determining the rate of unlawful gain is an important issue in Islamic banking in order to calculate Zakat of halal money, as well as to encourage Muslims to deal with Islamic banks.Therefore, the current study aims to produce a proposal including ratios and indicators of unlawful gain in Islamic banks through a critical and an analytical study of the ratios and indicators mentioned in some previous studies. Meanwhile, the study will suggest some accounting ratios to complement those ratios and indicators stated in the literature, and analyze them in a way to be useful for stakeholders and other investors.This study reached a number of conclusions and recommendations, the most important of which is the need for the attention of Islamic financial institutions to analyze the rates of unlawful gain, disclosure and methods of disposal, the actual measurement of the forbidden funds in the mixed money and when it is impossible to measure the estimated forbidden money with the reserve to take out what is more than most likely Pious and obedient.
Keywords: mixed funds; illegal gain; ratios and indicators; Islamic financial institutions; Accounting and Auditing Organization for Islamic Financial Institutions; Sharia violations in Islamic banks